Rightward exogenous attentional shifts impair perceptual memory of spatial locations in patients with left unilateral spatial neglect. (January 2020) - Saj, Arnaud; Pierce, Jordan; Caroli, Alice; Ronchi, Roberta; Thomasson, Marine; Vuilleumier, Patrik
Abstract: Spatial remapping implies the updating and maintaining of the spatial position of objects in successive visual images across time, despite their displacement on the retina due to eye movements. In the parietal cortex, the representation of spatial locations appears to be partly centered on gaze direction, and thus modulated by current eye-gaze position. It has been suggested that short-term memory for spatial locations across delays might be impaired in right brain-injured patients with left spatial neglect, but more so after rightward than leftward gaze shifts – an asymmetry attributed to a loss of spatial representations normally transferred from left to right hemisphere during remapping. Because several studies point to a strong link between attentional and oculomotor circuits in the brain, we hypothesized that similar remapping effects might result from attentional displacements without overt eye movements. We tested this hypothesis in right-brain damaged patients with and without left neglect in a visuo-spatial memory task. As predicted, neglect patients showed a selective deficit in location memory following an exogenous attentional shift caused by a brief flash in the periphery of their right (but not left) visual field. We conclude that an attentional displacement without eye movements is sufficient to remap spatial representations across hemifields, and that this process is impaired in neglect patients when a location has to be transferred to the neglected/left side relative to current gaze or attention focus. More generally, these results support the notion of neural overlap between oculomotor and attentional mechanisms, and confirm a role for impaired remapping in the neglect syndrome, wherein spatial representations of contralesional locations may fail to be maintained during active attentional behavior.